An efficient pilot scale solar treatment method for dye industry effluent using nano-ZnO. (April 2017) - Dhatshanamurthi, P.; Shanthi, M.; Swaminathan, M.
Highlights: Falling film photoreactor was used for pilot scale treatment of dye industry effluent. Thin film of prepared nano-ZnO is more stable, reusable under solar light. Maximum efficiency of catalyst at pH 7, makes it suitable for effluent treatment. Abstract: Fabrication of photocatalysts and photoreactors for treatment of industrial effluents has become vital to harness solar energy for environmental cleanup. Treatment of dye industry effluent by heterogeneous photocatalysis with prepared nano ZnO in falling film photoreactor under natural solar light has been investigated. Different weight proportions of slurry comprising fevicol and homemade ZnO were prepared and the fevicol- ZnO (F-Z)film on acrylic sheet was obtained by brush coating. Coating of ZnO with 10 wt% fevicol was found to be more adherent and efficient for dye degradation. This F-Z catalyst in the falling film photoreactor was tested for the treatment of dye effluent. F-Z catalyst prepared from nano-ZnO is more efficient than the catalysts made by commercial ZnO and TiO2-P25. The effects of operational parameters such as the amount of F-Z, effluent concentration, and initial pH on treatment process by F-Z coating as well as by suspended nano-ZnO slurry have been analyzed. Nano-ZnO is advantageous as its maximum efficiency occurs at neutral pH of 7. This pilot scale solar photocatalytic process can be widely applied at industrial scale.